Women and the Republican Party, 1854-1924 - Gustafson, Melanie S. (Women in American history., 2001)
"An examination of women's long history of participating in partisan politics, Women and the Republican Party, 1854-1924 explores the forces that propelled women to partisan activism in an era of widespread disfranchisement and provides a new perspective on how women fashioned their political strategies and identities before and after 1920." "Melanie Susan Gustafson examines women's partisan history as part of the larger history of women's political culture. Contesting the accepted notion that women were uninvolved in political parties before they formally got the vote, Gustafson reveals the length and depth of women's partisan activism between the founding of the Republican party, whose abolitionist agenda captured the loyalty of many women, and the passage of the Nineteenth Amendment."--Jacket